New insights on the upper layer circulation north of the Gulf of Guinea. Issue 9 (13th September 2016) - Herbert, G.; Bourlès, B.; Penven, P.; Grelet, J.
Abstract: The oceanic circulation in the upper layers of the north of the Gulf of Guinea is analyzed, as inferred from in situ observations and numerical simulations. This particular region, in spite of the presence of a coastal upwelling and its impact on resources and regional climate, is still poorly documented. Cruises carried out in the framework of different international programs (e.g., EGEE/AMMA, PIRATA) allowed to show the existence of an eastward flowing undercurrent, found under the Guinea Current, named the Guinea UnderCurrent (GUC). Numerical results from high resolution simulation allowed the description of the seasonal variability of this current. It appears that the GUC is stronger in spring and reverses westward in August–September. We also depict the fate and the sources of the GUC based on selected trajectories from numerical particle tracking. The simulated trajectories reveal: (i) a preferred route of the GUC along 4°N from Cape Palmas to Cape Three Points and following the coast east of Cape Three Points; (ii) strong recirculations in the most eastern part of the Gulf of Guinea and off Cape Palmas including warm and salty waters of the South Equatorial Current; (iii) a weak inflow from northern latitudes through a subsurface current flowing southward along the West African coast. In addition, Lagrangian experiments show that the GUC is not an extension of the North Equatorial UnderCurrent and confirm that this current does not penetrate into the Gulf of Guinea. Key Points: A 100/250 m depth eastward current observed north of 4°N in the Gulf of Guinea: the Guinea UnderCurrent The Guinea UnderCurrent is stronger in spring and reverses westward in August–September It is fed from recirculation current system and a weak subsurface current flowing along the West African coast